The Art of Dabus Indragiri in Rantau Mapesai as a Medium to Build Character - Wijaya, Dhimayu Ichtiara; Triyanto, Triyanto (Catharsis, 2018)
The art of Dabus Indragiri is an art which shows the body’s resistance to sharp objects by performing dance and Berzanji music accompaniment. Rarely is the art of Dabus Indragiri performed in Rantau Mapesai nowadays. However, there is an awareness from artists to preserve this art because it has values to build character. Based on the above information, this research was to study the values of character which were contained in the art of Dabus Indragiri. The Method used was qualitative. The research was located in Rantau Mapesai, Indragiri Hulu Regency. The data were gathered by doing observation, interview, document study. The technique of data validity used sources trangulation. The technique of data analysis used descriptive analysis. The results stated that the character values in Dabus Indragiri are; (1) religious, (2) like to read, (3) responsible, (4) social care (5) creative, (6) having spirit of nationality, (7) love the homeland, (8) hard work, (9) independent (10) care of environment, (11) friendly or communicative. According to the results, we can conclude that the art of Dabus Indragiri can build character.